The Ethical Dilemmas and Social Scientific Trade-offs of Masking in Ethnography. (November 2019) - Jerolmack, Colin; Murphy, Alexandra K.
Masking, the practice of hiding or distorting identifying information about people, places, and organizations, is usually considered a requisite feature of ethnographic research and writing. This is justified both as an ethical obligation to one's subjects and as a scientifically neutral position (as readers are enjoined to treat a case's idiosyncrasies as sociologically insignificant). We question both justifications, highlighting potential ethical dilemmas and obstacles to constructing cumulative social science that can arise through masking. Regarding ethics, we show, on the one hand, how masking may give subjects a false sense of security because it implies a promise of confidentiality that it often cannot guarantee and, on the other hand, how naming may sometimes be what subjects want and expect. Regarding scientific tradeoffs, we argue that masking can reify ethnographic authority, exaggerate the universality of the case (e.g., "Middletown"), and inhibit replicability (or "revisits") and sociological comparison. While some degree of masking is ethically and practically warranted in many cases and the value of disclosure varies across ethnographies, we conclude that masking should no longer be the default option that ethnographers unquestioningly choose.